Hindī nāṭaka, 1960 ke bāda - Kumar, Bachan Deo, 1934- (Vibhu Prakāśana ; distributors, Classical Pub. Co., 1982)
Articles on the post-1960 Hindi drama; includes an exhaustive list of post-1960 Hindi titles.